Production of a Milk‐Clotting Enzyme by Glutinous Rice Fermentation and Partial Characterization of the Enzyme. Issue 1 (15th January 2015) - Zhao, Xiao; Wang, Ji; Zheng, Zhe; Zhao, Aimei; Yang, Zhennai
Abstract Fermentation parameters affecting a milk‐clotting enzyme (MCE) production by glutinous rice fermentation were evaluated using selected rice starters called Jiuqu. The MCE was produced under the following conditions: rice inoculation starter at 3%, fermentation time of 5 days, temperature at 30C, initial rice medium pH of 5.0, rice concentration of 70% and rotation speed of 120 rpm. The enzyme preparation obtained by 70% ethanol precipitation of the culture supernatant had milk‐clotting activity (MCA) of 6, 160 Su/g and a C/P ratio (the ratio between MCA and proteolytic activity) of 10.81 at a recovery rate of 44.82%. The molecular mass of the MCE was 39.7 kDa. MCE production was optimal at 35C and a pH of 5.4. The presence of Na+, K+, Mg2+, Ca2+ and Al3+ stimulated enzyme activity. The Km and Vmax values were 22.90 g/L and 21.11 mL/s, respectively, with skim milk as the substrate. Practical Applications In the last two decades, different sources of milk‐clotting enzymes (MCEs) have been explored to meet the increasing demand for cheese production worldwide. This study describes a MCE isolated by ethanol fractionation from glutinous rice wine fermented by Jiuqu. The MCE, with a relatively high C/P ratio, is potentially applicable as a coagulant in cheese making. The property of thermal instability of the enzyme is advantageous as it would be inactivated during curd scalding (at about 50C), thus formation of bitter‐taste peptides caused by residual proteolytic activity of the enzyme during cheese ripening could be prevented. In addition, the optimal temperature (35C) of the MCE is within the range of temperature (30–35C) generally used during milk coagulation processes. Therefore, the results suggest that a MCE that could have potential application in cheese production may be obtained by glutinous rice fermentation under the conditions of this study.